2023
DOI: 10.1097/ms9.0000000000000381
|View full text |Cite
|
Sign up to set email alerts
|

Successful surgical management of primary hyperparathyroidism during pregnancy: a rare case report

Abstract: Introduction: Primary hyperparathyroidism (PHPT) in pregnancy is a rare condition. Because of gestational physiologic changes, it is easily under-recognized; in some cases, patients may remain symptomless while maintaining high serum calcium levels, posing a risk to the health of both mother and fetus. Case Presentation: Our patient is a pregnant woman in her 30th week of gestation admitted to the hospital with typical features of acute pancreatitis. All possible causes of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 18 publications
0
0
0
Order By: Relevance
“…A particular entity is represented by acute pancreatitis with gestational primary hyperparathyroidism (representing less than 1–2% of all female cases that present a parathyroid NET) [ 31 ]. Acute severe hypercalcemia complicated or not [ 36 ] with acute pancreatitis has been reported in gestation as the first diagnosis [ 37 , 38 , 39 ], particularly in young females associated with genetic forms of hyperparathyroidism [ 40 ]. Sometimes, acute hypercalcemia triggers or mimics eclampsia/pre-eclampsia and complicates maternal/fetal outcomes, while parathyroidectomy might be necessary during pregnancy if medical therapy fails to control the abnormal serum calcium levels; alternatively, in other cases, an emergency cesarean is performed, and postpartum parathyroidectomy is later provided [ 38 ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…A particular entity is represented by acute pancreatitis with gestational primary hyperparathyroidism (representing less than 1–2% of all female cases that present a parathyroid NET) [ 31 ]. Acute severe hypercalcemia complicated or not [ 36 ] with acute pancreatitis has been reported in gestation as the first diagnosis [ 37 , 38 , 39 ], particularly in young females associated with genetic forms of hyperparathyroidism [ 40 ]. Sometimes, acute hypercalcemia triggers or mimics eclampsia/pre-eclampsia and complicates maternal/fetal outcomes, while parathyroidectomy might be necessary during pregnancy if medical therapy fails to control the abnormal serum calcium levels; alternatively, in other cases, an emergency cesarean is performed, and postpartum parathyroidectomy is later provided [ 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…Sometimes, acute hypercalcemia triggers or mimics eclampsia/pre-eclampsia and complicates maternal/fetal outcomes, while parathyroidectomy might be necessary during pregnancy if medical therapy fails to control the abnormal serum calcium levels; alternatively, in other cases, an emergency cesarean is performed, and postpartum parathyroidectomy is later provided [ 38 ]. We identified five single case reports of this specific circumstance (age at presentation of 26, 30, 31—for two patients—and 40 years; two of these women developed postpartum pancreatitis [ 38 , 41 ]) [ 37 , 38 , 39 , 41 , 42 ] and one of the previously mentioned studies [ 31 ]. For example, Dias Leite et al [ 41 ] reported on a 40-year-old primigravida who was admitted as an emergency case for pre-eclampsia at week 27 of gestation.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations